Wall in front entrance of a home in Stephenville with picture - Marche, Patrick Sean (1978)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « A Description of a House in Stephenville, Newfoundland ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "A Description of a House in Stephenville, Newfoundland"